2022
DOI: 10.1093/jas/skac354
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of graded levels of corn-fermented protein on stool quality, apparent nutrient digestibility, and palatability in healthy adult cats

Abstract: Dried distillers’ grains, co-products from the ethanol industry, may provide sustainable ingredients for pet food. Due to new post-fermentation separation techniques, corn fermented protein (CFP) is higher in protein and lower in fiber compared to traditional dried distillers’ grains, increasing its appeal for inclusion into pet food. Therefore, the objectives of this study were to determine the effects of increasing levels of CFP on stool quality, apparent total tract digestibility (ATTD), and palatability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The protein is mostly distributed between the endosperm and the germ; meanwhile, the coarse fiber is a characteristic composition of the epidermis [ 38 ]. In general, when maize was used as feed, the lower fiber content and higher protein content were often considered to have better palatability [ 39 ]. From the results, the effect of cold plasma treatment on the quality of maize is generally acceptable, and it can even improve the quality in some aspects.…”
Section: Resultsmentioning
confidence: 99%
“…The protein is mostly distributed between the endosperm and the germ; meanwhile, the coarse fiber is a characteristic composition of the epidermis [ 38 ]. In general, when maize was used as feed, the lower fiber content and higher protein content were often considered to have better palatability [ 39 ]. From the results, the effect of cold plasma treatment on the quality of maize is generally acceptable, and it can even improve the quality in some aspects.…”
Section: Resultsmentioning
confidence: 99%
“…The digestibility of diets containing increasing levels of CFP when fed to dogs differed relative to that observed in cats. Kilburn-Kappeler et al (2022) reported that digestibility of diets containing 5% and 10% CFP was comparable to the control when fed to cats. However, a significant decrease in digestibility was observed when cats were fed diets containing 15% CFP.…”
Section: Apparent Total Tract Digestibilitymentioning
confidence: 96%
“…The palatability of CFP in dogs differed from that in cats. Wherein, Kilburn-Kappeler et al (2022) observed that cats preferred a 5% inclusion of CFP compared with a control (0% CFP), but had no preference with increased inclusion levels (10% and 15% CFP). However, in the current study, dogs had no preference between the control and the low inclusion level (5% CFP), but appeared to prefer the control over the higher CFP inclusion levels of 10% and 15%.…”
Section: Palatabilitymentioning
confidence: 96%
See 2 more Smart Citations